The Constitutionality of sections 56 and 57 of the Central Bank of Malaysia Act 2009: JRI Resources Sdn Bhd v Kuwait Finance - Kunhibava, Sherin; Yeo, Valerie Li Ann (Journal of Malaysian and Comparative Law, 2019)
The Federal Court of Malaysia sitting for the first time on a nine-bench panel passed a landmark decision on Islamic banking and finance on 10 April 2019. It ruled through a majority of five that ss 56 and 57 of the Central Bank of Malaysia Act 2009 (`CBMA') was constitutional and that the Shariah Advisory Council's role was no more than that of an expert body giving evidence. This case note will begin with the legal background of ss 56 and 57 CBMA and will then discuss both the majority and minority decisions of the case before analysing it.